Primary Osteoporosis Is Not Reflected by Disease‐Specific DNA Methylation or Accelerated Epigenetic Age in Blood. (23rd October 2017) - Fernandez‐Rebollo, Eduardo; Eipel, Monika; Seefried, Lothar; Hoffmann, Per; Strathmann, Klaus; Jakob, Franz; Wagner, Wolfgang
ABSTRACT: Osteoporosis is an age‐related metabolic bone disease. Hence, osteoporotic patients might suffer from molecular features of accelerated aging, which is generally reflected by specific age‐associated DNA methylation (DNAm) changes. In this study, we analyzed genomewide DNAm profiles of peripheral blood from patients with manifest primary osteoporosis and non‐osteoporotic controls. Statistical analysis did not reveal any individual CG dinucleotides (CpG sites) with significant aberrant DNAm in osteoporosis. Subsequently, we analyzed if age‐associated DNAm patterns are increased in primary osteoporosis (OP). Using three independent age‐predictors we did not find any evidence for accelerated epigenetic age in blood of osteoporotic patients. Taken together, osteoporosis is not reflected by characteristic DNAm patterns of peripheral blood that might be used as biomarker for the disease. The prevalence of osteoporosis is age‐associated—but it is not associated with premature epigenetic aging in peripheral blood. © 2017 American Society for Bone and Mineral Research.